2015
DOI: 10.1016/j.mce.2015.01.044
|View full text |Cite
|
Sign up to set email alerts
|

Helix 8 of the ligand binding domain of the glucocorticoid receptor (GR) is essential for ligand binding

Abstract: Membrane association of estrogen receptors (ER) depends on cysteine palmitoylation and two leucines in the ligand binding domain (LBD), conserved in most steroid receptors. The role of this region, corresponding to helix 8 of the glucocorticoid receptor (GR) LBD, on membrane association of GR was studied in 4B cells, expressing endogenous GR, and Cos-7 cells transfected EGFP-GR constructs. 4B cells preloaded with radiolabeled palmitic acid showed no radioactivity incorporation into immunoprecipitated GR. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…In the case of the ER, these nongenomic actions are mediated by membrane association of the receptor. In agreement with previous immunohistochemical (14 -17), and western blot studies (24), the present experiments show association of the classical GR to membrane fractions in AtT-20 and 4B cell lines. This ligand-dependent increase in membrane GR was not due to contamination with nuclear proteins as shown by the absence of nuclear markers in membrane proteins.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the case of the ER, these nongenomic actions are mediated by membrane association of the receptor. In agreement with previous immunohistochemical (14 -17), and western blot studies (24), the present experiments show association of the classical GR to membrane fractions in AtT-20 and 4B cell lines. This ligand-dependent increase in membrane GR was not due to contamination with nuclear proteins as shown by the absence of nuclear markers in membrane proteins.…”
Section: Discussionsupporting
confidence: 93%
“…The lower corticosterone concentration used, 10 nM increased nuclear immunoreactive GR by 2.8 Ϯ 0.4-fold (P Ͻ .01) and much larger increases of 6.5 Ϯ 0.3 and 7.5 Ϯ 0.1 were observed with 100 nm and 1 M, corticosterone respectively ( Figure 6). As previously described in 4B cells (24), a band corresponding to irGR was also observed in membrane protein fractions colocalized with pancadherin. One way ANOVA also showed a significant effect of corticosterone on GR levels in membrane proteins (F ϭ 11.1, P Ͻ .002).…”
Section: Corticosterone Induces Association Of Gr To Membrane Proteinssupporting
confidence: 80%
See 1 more Smart Citation
“…52 However, the nature of this membrane-anchoring GR has not yet been clarified. Although most of the steroid receptors were shown to incorporate palmitic acid, a post-translational modification termed "S-palmitoylation" that enables membrane binding of proteins and increases protein hydrophobicity, 53,54 we and others have demonstrated that GRα does not undergo S-palmitoylation, implying that other mechanisms are responsible for GRα membrane localization and mediate the nongenomic glucocorticoid actions [55][56][57] (Figure 2). …”
Section: Genomic Nongenomic and Mitochondrial Gr Signalingmentioning
confidence: 99%
“…However, the lack of rapid effects of dexamethasone in hypothalamic slices of mice bearing targeted deletion of GR in the PVN, strongly suggests that the classical GR mediates non-genomic effects [43]. Supporting the involvement of the classical GR in mediating the rapid effects of glucocorticoids, immunohistochemical and biochemical studies have shown membrane localization of GR in a number of systems [26,[44][45][46][47].…”
Section: Glucocorticoid Feedback Inhibits Crh Secretion and Expressionmentioning
confidence: 99%